2012
DOI: 10.1371/journal.pone.0050433
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Patterns of Human-Wildlife Conflicts and Compensation around a Central Indian Protected Area

Abstract: Mitigating crop and livestock loss to wildlife and improving compensation distribution are important for conservation efforts in landscapes where people and wildlife co-occur outside protected areas. The lack of rigorously collected spatial data poses a challenge to management efforts to minimize loss and mitigate conflicts. We surveyed 735 households from 347 villages in a 5154 km2 area surrounding Kanha Tiger Reserve in India. We modeled self-reported household crop and livestock loss as a function of agricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
97
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(114 citation statements)
references
References 33 publications
10
97
6
Order By: Relevance
“…Similar to other multipredator systems where felids typically killed fewer livestock than other predators (e.g., Rigg et al 2011, Karanth et al 2012, cougar livestock incidents were the lowest of all carnivores in our study despite an expanding and increasing population (Knopff et al 2014). Although cougars occasionally kill livestock, cougar diet in southwestern Alberta, like many regions of North America, is primarily deer (Anderson and Lindzey 2003, Knopff et al 2009, Bacon et al 2011, Banfield 2012.…”
Section: Discussionsupporting
confidence: 74%
“…Similar to other multipredator systems where felids typically killed fewer livestock than other predators (e.g., Rigg et al 2011, Karanth et al 2012, cougar livestock incidents were the lowest of all carnivores in our study despite an expanding and increasing population (Knopff et al 2014). Although cougars occasionally kill livestock, cougar diet in southwestern Alberta, like many regions of North America, is primarily deer (Anderson and Lindzey 2003, Knopff et al 2009, Bacon et al 2011, Banfield 2012.…”
Section: Discussionsupporting
confidence: 74%
“…The compensation program also offers tractable longterm data that can be used for assessing the temporal and spatial patterns and physical characteristics of livestock losses. Kill data offer exclusive fine-scale spatial information about the sites where livestock are vulnerable to livestock, offering a unique perspective not otherwise captured by household surveys, which have been the basis of many previous studies on human-carnivore conflict (e.g., Wang and Macdonald 2006;Nugraha and Sugardjito 2009;Karanth et al 2012;Katel et al 2014;Bhattarai and Fischer 2014).…”
Section: Discussionmentioning
confidence: 99%
“…To receive compensation, a livestock owner must locate and report the livestock carcass to the Forest Department within 48 h, and an officer then visits the site to record evidence of the death. Although not all livestock owners choose to report lost livestock (Karanth et al 2012), between 400 and 600 livestock are reported for compensation each year within the tiger reserve (Negi and Shukla 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trust is essential and can be facilitated by developing a coordinated response to immediately mitigate and resolve predator-livestock issues in the Central Indian Highlands protected areas, buffer zones, and corridors (Karanth et al 2012). Just as important is to be proactive and identify risk zones (Miller 2014).…”
Section: Priority Actions On Which To Build a Collectiveengagement Plmentioning
confidence: 99%